2012
DOI: 10.1080/87568225.2012.685856
|View full text |Cite
|
Sign up to set email alerts
|

Counseling on Campus: Client Persistence and Progress

Abstract: Two related studies addressed college students' persistence and progress in psychotherapy. In Study 1, using emotional health variables assessed at intake, students who persisted in counseling and demonstrated clinical improvement were compared with those who either did not return for their first session or who did return but stopped before improvement. Findings showed that those counseling completers, compared with the other two groups, reported at intake significantly higher levels of confidence that therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
5
7
0
Order By: Relevance
“…These overall improvement results are also consistent with Lucas (2012) who found significant improvement in the "highly distressed" undergraduate client sub-sample between intake and their eighth session, and Wolgast et al (2004) who showed that 14 sessions were needed for clients to show clinically significant change. Such research supports having the resources available in a UCC to avoid "time limited" treatment (Ghetie, 2007).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…These overall improvement results are also consistent with Lucas (2012) who found significant improvement in the "highly distressed" undergraduate client sub-sample between intake and their eighth session, and Wolgast et al (2004) who showed that 14 sessions were needed for clients to show clinically significant change. Such research supports having the resources available in a UCC to avoid "time limited" treatment (Ghetie, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…There were only 15 participants in the complete-data sample. Although such client loss is consistent with prior research (e.g., Draper et al, 2002;Ghetie, 2007;Lucas, 2012;Mahon et al, 2015), it was none-the-less discouraging. The four-year data collection has stopped due to several reasons, including the UCC moving to a new location and some key staff turnover, but general lack of client response was the primary issue.…”
Section: Study Limitationssupporting
confidence: 72%
See 2 more Smart Citations
“…Institutional Review Board (IRB) approval was given for all data collection, and data were collected using online surveys which went directly into Qualtrics' data bases. Lucas (2012) used a similar three-year period (2004 to 2007) to collect an undergraduate counseling sample. These undergraduate students had been designated at their initial counseling session (i.e., an in-person triage interview), as non-urgent (non-suicidal or risk to self/others) by the triage therapist.…”
Section: Samples and Proceduresmentioning
confidence: 99%